Comparison of expert-rater methods for assessing psychosocial job strain - Ostry, Aleck S; Marion, Stephen A; Demers, Paul A; Hershler, Ruth; Kelly, Shona; Teschke, Kay; Mustard, Cameron; Hertzman, Clyde (Scandinavian Journal of Work, Environment & Health, 2001)
' ' OBJECTIVES ': 'This study tested the reliability and validity of industry- and mill-level expert methods for measuring psychosocial work conditions in British Columbia sawmills using the demand-control model. ' ' METHODS ': 'In the industry-level method 4 sawmill job evaluators estimated psychosocial work conditions at a generic sawmill. In the mill-level method panels of experienced sawmill workers estimated psychosocial work conditions at 3 sawmills. Scores for psychosocial work conditions were developed using both expert methods and applied to job titles in a sawmill worker database containing self-reported health status and heart disease. The interrater reliability and the concurrent and predictive validity of the expert rater methods were assessed. ' ' RESULTS ': 'The interrater reliability and concurrent reliability were higher for the mill-level method than for the industry-level method. For all the psychosocial variables the reliability for the mill-level method was greater than 0.90. The predictive validity results were inconclusive. ' ' CONCLUSIONS ': 'The greater reliability and concurrent validity of the mill-level method indicates that panels of experienced workers should be considered as potential experts in future studies measuring psychosocial work conditions.
Keywords: expert assessment; expert-rater method; psychosocial job strain; psychosocial work conditions; reliability; sawmill; validity